Kohäsion und soziales Kapital : Ausschließungsprozesse in der Sozialen Arbeit - Landhäußer, Sandra (Sozialmagazin)
Soziale Arbeit rückt im Zusammenhang mit der Thematisierung eines geringen gesellschaftlichen Zusammenhalts in den Vordergrund, wenn vermehrte Kohäsion mit der Aktivierung sozialen Kapitals erreicht werden soll. Vor diesem Hintergrund wird eine auf politischer Ebene prominente Version sozialen Kapitals sowie ihr Beitrag zur Erhöhung gesellschaftlichen Zusammenhalts genauer untersucht und auf seine Aussagekraft für die Soziale Arbeit hin befragt.

Detection of cyclostationarity in the presence of temporal or spatial structure with applications to cognitive radio - Pries, Aaron; Ramírez, David; Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
One approach to spectrum sensing for cognitive radio is the detection of cyclostationarity. We extend an existing multi-antenna detector for cyclostationarity proposed by Ramírez et al. [1], which makes no assumptions about the noise beyond being (temporally) wide-sense stationary. In special cases, the noise could be uncorrelated among antennas, or it could be temporally white. The performance of a general detector can be improved by making use of a priori structural information. We do not, however, require knowledge of the exact values of the temporal or spatial noise covariances. We develop an asymptotic generalized likelihood ratio test and evaluate the performance by simulations.

Flag-based detection of weak gas signatures in long-wave infrared hyperspectral image sequences. - Marrinan, Tim; Beveridge, J. Ross; Draper, Bruce; Kirby, Michael; Peterson, Chris (SPIE Defense, Security, and Sensing)

A unified scheme to achieve the degrees-of-freedom region of the MIMO interference channel with delayed channel state information - Rezaee, Mohsen; Schreier, Peter J.; Guillaud, M.; Clerckx, B. (IEEE Trans.\ Comm.)

Analysis of the downlink saturation throughput of an asymmetric IEEE 802.11 n-based WLAN - Soleymani, Mohammad; Maham, Behrouz; Ashtiani, Farid (Proc. IEEE International Conference on Communications (ICC))

Sample-poor estimation of order and common signal subspace with application to fusion of medical imaging data - Levin-Schwartz, Y.; Song, Yang; Schreier, Peter J.; Calhoun, V.D.; Adali, Tülay (NeuroImage)

Cross-validation techniques for determining the number of correlated components between two data sets when the number of samples is very small - Lameiro, Christian; Schreier, Peter J. (Proc.\ Asilomar Conf.\ Signals Syst.\ Computers)

Maximally improper interference in underlay cognitive radio networks - Lameiro, Christian; Santamaría, I.; Utschick, W.; Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Measurement-driven quality assessment of nonlinear systems by exponential replacement - Stein, Manuel; Nossek, Josef A.; Barbé, Kurt (Proc.\ IEEE Int. Instrum. & Meas. Tech.\ Conf.)

Analysis of the downlink saturation throughput of an asymmetric IEEE 802.11 n-based WLAN - Soleymani, Mohammad; Maham, Behrouz; Ashtiani, Farid (Proc. IEEE International Conference on Communications (ICC))

Rezension von Ernst Kapp: Grundlinien einer Philosophie der Technik. Über die Entstehung der Kulturgeschichte aus neuen Gesichtspunkten - Alpsancar, Suzana (Technikgeschichte)

Das Darmstädter Modell: Entwicklungspotentiale für die Interdisziplinaritäten in der Lehre - Alpsancar, Suzana; Denker, Kai; Gehring, Petra; Terizakis, Georgios; Abdelhamid, Michaela; Brenneis, Andreas; Grill, Annika; Frehe, Hardy; Tulatz, Kaja

Mode Macht Körper – wie die Materialität von Kleidung Modekörper und Körper definiert - Haller, Melanie; Villa, Paula-Irene; Schadler (Hg.), Corinna (Becoming with Things – Bodies, Objects, Practice, Themenheft der Zeitschrift Body Politics, Heft 9, 2016. Link: http://bodypolitics.de/de/das-aktuelle-heft/ (16.07.2017).)

Tango Argentino und seine Mode – Bewegungsfreiheiten und Kleiderordnungen - Haller, Melanie; Rieger (Hg.), Rita (Bewegungsfreiheit. Tanz als kulturelle Manifestation (1900-1950), Graz 2017.)

Evaluation der Reflexion: Wissenschaftliche Begleitung eines Projekts zur Überprüfung eines semesterübergreifenden Begleitangebots auf spezifische Aspekte der Persönlichkeit. - Seifert, Andreas; Balsam, Rebecca; Newig, Jens (Professionalisierung der Hochschuldidaktik)

Can 28-month-old children learn spatial prepositions robustly from pictures? Yes, when narrative input is provided. - Rohlfing, Katharina; Nachtigäller, Kerstin (Frontiers in Language Science)

Analysis of individual and systematic determinants regarding arithmetic skills of first graders. - Seifert, Andreas; Eilerts, Katja; Rinkens, Hans-Dieter (13th International Congress on Mathematical Education (ICME).)

Der Einfluss individueller und institutioneller Faktoren auf die Kompetenzeinschätzung von Studierenden im Praxissemester. - Festner, Dagmar; Gröschner, Alexander; Seifert, Andreas (4. Tagung der Gesellschaft der Empirischen Bildungsforschung (GEBF))

Analysekompetenz – ein mehrdimensionales Konstrukt. - Scholl, Daniel; Seifert, Andreas (DGFE-Kongress „Räume für Bildung. Räume der Bildung.“)

Bühnenrollen und Identitätskonzepte: Karrierestrategien von Künstlerinnen im Theater des 19. Jahrhunderts